2021
DOI: 10.1016/j.celrep.2021.109656
|View full text |Cite
|
Sign up to set email alerts
|

Cilium induction triggers differentiation of glioma stem cells

Abstract: Highlights d Cilium checkpoint regulates self-renewal and differentiation of neural stem cells d GSCs have suppressed ciliogenesis and thus have no cilium checkpoint d Reintroducing of cilia in GSCs switches them from selfrenewal to differentiation state d GSCs reintroduced with cilia do not invade brain organoids

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 76 publications
1
34
0
Order By: Relevance
“…Cilia are key organelles not only involved in cell movement but are also major regulators of cell proliferation [ 40 ]. Most cells begin to disassemble their primary cilia at cell cycle re-entry [ 41 ] and reintroduction of cilia genes in cancer cells can lead to proliferation arrest and differentiation [ 42 ]. Remarkably, GO analysis revealed a significant downregulation of these genes after SCI ( Figure 1 D and Table S1 ) suggesting a link with the concomitant upregulation of genes involved in mitosis ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
“…Cilia are key organelles not only involved in cell movement but are also major regulators of cell proliferation [ 40 ]. Most cells begin to disassemble their primary cilia at cell cycle re-entry [ 41 ] and reintroduction of cilia genes in cancer cells can lead to proliferation arrest and differentiation [ 42 ]. Remarkably, GO analysis revealed a significant downregulation of these genes after SCI ( Figure 1 D and Table S1 ) suggesting a link with the concomitant upregulation of genes involved in mitosis ( Figure 1 D).…”
Section: Resultsmentioning
confidence: 99%
“…Further support for the tumor-suppressing role of cilia in GBM was recently reported by Goranci-Buzhala et al (2021) who showed that patient-derived glioblastoma stem cells displayed high levels of proteins that are involved in cilia disassembly such as CPAP, Aurora-A, NEK2, NDE1 and OFD1 that resulted in suppressing ciliogenesis. Furthermore, patient-derived glioblastoma stem cells and clinical glioblastoma tissue displayed reduced primary cilia formation associated with increased cell proliferation.…”
Section: Primary Cilia and Brain Tumorsmentioning
confidence: 65%
“…Furthermore, patient-derived glioblastoma stem cells and clinical glioblastoma tissue displayed reduced primary cilia formation associated with increased cell proliferation. Importantly, rescuing ciliogenesis by depleting the disassembly protein complex restored cilia formation and non-malignant phenotype, as glioma stem cells were able to trigger differentiation ( Goranci-Buzhala et al, 2021 ). Strikingly, ciliogenesis-induced differentiation was critical to prevent infiltration of glioma stem cell organoids into the brain of mice showing that signals from the primary cilia determine glioma stem cell fate ( Goranci-Buzhala et al, 2021 ).…”
Section: Primary Cilia and Brain Tumorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cancer stem cell hypothesis predates human pluripotent stem cell technology though still remains controversial (see Gimple et al, 2019 for a recent review). Methods for isolation and culture of CNS solid tumor stem cells are established and can be used for examining the first steps of cancer formation (see Goranci-Buzhala et al, 2021 for a recent example). Human stem cells (endogenous and PSC-derived) make excellent complimentary models for studying the cell of origin, cellular heterogeneity, and mechanisms of progression of multiple types of brain cancers, particularly since dedifferentiation and re-activation of an embryonic stem-like state is a hallmark of many cancers.…”
Section: Complementing and Building On Animal Models With Human Stem Cell Modelsmentioning
confidence: 99%